AUTOMATION OF TECHNOLOGICAL OPERATIONS IN THE MANUFACTURE OF WOODEN TOYS - Radkova, Izabela; Petrova, Zornica (Innovation in Woodworking Industry and Engineering design, 2020)
Traditional universal and specialized woodworking machines perform the industrial production of details for toys made of solid wood. The automation of such discrete technological processes and operations can be accomplished by designing and implementing automated complexes that provide high performance. The report presents three effective solutions for automated complexes for the automation of technological operations in the production of rotary details for toys of solid wood. These are key factors for automating discrete processes and specific prospects for the development and automation of the production of wooden toys. Specific solutions are shown to automate the flow of details when processing the rotary parts. A theoretical analysis was carried out and cyclograms of the work of the specific automated complexes were presented.